Weaknesses of the Change from the Official System to the Self Assessment System: Completeness of Tax Data 2023-2024 - Kuncoro, Amin; Afandi, Pandi (Global Health Science Group, 2025)
The transition from the Official Assessment System to the Self-Assessment One of the major challenges is the increasing risk of non-compliance due to inaccurate or deliberately manipulated tax reporting. Another significant weakness is the increasing demand for strict monitoring and enforcement mechanisms. Tax authorities must improve their audit capabilities and apply stringent sanctions to ensure optimal compliance. However, such enforcement measures require substantial resources, including skilled personnel and sophisticated information technology systems. The study uses a qualitative approach aimed at analyzing the weaknesses arising from the transition from the Official Assessment System to the Self-Assessment System and evaluating their impact on tax compliance and revenue effectiveness. The findings are expected to provide policy recommendations for improving the tax system to improve compliance and ensure sustainable tax revenue collection.